2020
DOI: 10.1186/s12885-020-07034-6
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic characterization of OAS1/OAS2/OAS3/OASL in breast cancer

Abstract: Background: Prognostic biomarkers remain a focus in breast cancer during last decades. More reliable predictors to adequately characterize the prognosis of breast cancer are essential. The 2′-5′-oligoadenylate synthetases (OAS), composing of OAS1, OAS2, OAS3, and OAS-like (OASL), are interferon (IFN)-induced antiviral enzymes, with their prognostic roles remain to be characterized. Methods: Prognostic values of OAS family members were assessed by multiple public available resources.Results: High mRNA expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
57
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 28 publications
5
57
3
Order By: Relevance
“…Our analysis identified a number of common dysregulated genes between COVID-19 and cancers. Among the identified common genes, MARCO and OAS2 were identified as dysregulated in breast cancer as consistent with previous report [ 38 , 39 ]. Previous studies suggested OAS2 as prognostic markers of breast cancer [ 39 ].…”
Section: Discussionsupporting
confidence: 91%
“…Our analysis identified a number of common dysregulated genes between COVID-19 and cancers. Among the identified common genes, MARCO and OAS2 were identified as dysregulated in breast cancer as consistent with previous report [ 38 , 39 ]. Previous studies suggested OAS2 as prognostic markers of breast cancer [ 39 ].…”
Section: Discussionsupporting
confidence: 91%
“…OASL expression showed a significant correlation with neutrophil infiltration. Consistently, Zhang et al also found that OAS1 and OASL were correlated to neutrophil cell infiltration in breast cancer ( 33 ). Thus, MET, OAS1, and OASL were distinctly correlated to tumor immune microenvironment.…”
Section: Discussionmentioning
confidence: 53%
“…The OASL gene has been found to be associated with the regulation of lung cancer cell sensitivity to acRoots, via the PI3K signal pathway [ 46 ]. OASL has also been associated with proliferation of cancer such as that of the gastric and breast type, and therefore can play a role in prognostication with potential mechanistic value in breast cancer [ 47 ]. Lohavanichbutr P et al, using L1/L2-penalized Cox regression models in HPV-negative OSCC, identified six genes, one of which was OASL, and reported that all these genes play a role in cell invasion and motility, cell-to-cell signaling, signal transduction, and proliferation, processes essential to metastasis and cancer progression [ 48 ].…”
Section: Discussionmentioning
confidence: 99%